Association of skeletal muscle mass and risk of hypertension in Korean adults: secondary analysis of data from the community-based prospective cohort study - Bu, So Young (Frontiers in Nutrition, 2023)
Background: Cross-sectional studies have revealed a link between low muscle mass and hypertension. However, whether the degree of muscle mass predicts hypertension risk has not been confirmed. This study aimed to verify an association between skeletal muscle mass and incident hypertension in a longitudinal follow-up of middle-aged Korean adults.The community-based prospective Korean Genome and Epidemiology Study (KoGES) study analyzed data from 2,669 participants who were free of hypertension at baseline and were prospectively assessed at 2-year intervals for 16 years. The participants were divided into tertiles T1-T3 of relative skeletal muscle mass (RSM) according to their baseline whole-body skeletal muscle mass measured as bioelectrical impedance. Incident hypertension was estimated using multivariate logistic regression with the Cox proportional hazard regression model.Results: Over the 16-year follow-up, the rates of incident hypertension at RSM T1, T2, and T3 were 18.7%, 17.1%, and 13.4% in men (P for trend = 0.0002) and 18.8%, 14.7%, and 12.9% in women (P for trend = 0.0007), respectively. The multivariate adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) for the incidence of hypertension for men and women in T1 and T2 were 1.